An ESPGHAN Position Paper on the Use of Breath Testing in Paediatric Gastroenterology. Issue 1 (January 2022) - Broekaert, Ilse Julia; Borrelli, Osvaldo; Dolinsek, Jernej; Martin-de-Carpi, Javier; Mas, Emmanuel; Miele, Erasmo; Pienar, Corina; Ribes-Koninckx, Carmen; Thomassen, Rut; Thomson, Mike; Tzivinikos, Christos; Benninga, Marc
ABSTRACT: Objectives: Given a lack of a systematic approach to the use of breath testing in paediatric patients, the aim of this position paper is to provide expert guidance regarding the indications for its use and practical considerations to optimise its utility and safety. Methods: Nine clinical questions regarding methodology, interpretation, and specific indications of breath testing and treatment of carbohydrate malabsorption were addressed by members of the Gastroenterology Committee (GIC) of the European Society for Paediatric Gastroenterology Hepatology and Nutrition (ESPGHAN). A systematic literature search was performed from 1983 to 2020 using PubMed, the MEDLINE and Cochrane Database of Systematic Reviews. Grading of Recommendations, Assessment, Development, and Evaluation was applied to evaluate the outcomes. During a consensus meeting, all recommendations were discussed and finalised. In the absence of evidence from randomised controlled trials, recommendations reflect the expert opinion of the authors. Results: A total of 22 recommendations were voted on using the nominal voting technique. At first, recommendations on prerequisites and preparation for as well as on interpretation of breath tests are given. Then, recommendations on the usefulness of H2-lactose breath testing, H2-fructose breath testing as well as of breath tests for other types of carbohydrate malabsorption are provided. Furthermore, breath testing is recommended to diagnose small intestinal bacterial overgrowth (SIBO), to control for success of Helicobacter pylori eradication therapy and to diagnose and monitor therapy of exocrine pancreatic insufficiency, but not to estimate oro-caecal transit time (OCTT) or to diagnose and follow-up on celiac disease. Conclusions: Breath tests are frequently used in paediatric gastroenterology mainly assessing carbohydrate malabsorption, but also in the diagnosis of small intestinal overgrowth, fat malabsorption, H. pylori infection as well as for measuring gastrointestinal transit times. Interpretation of the results can be challenging and in addition, pertinent symptoms should be considered to evaluate clinical tolerance.